Linkage of the Medical Education Partnership Initiative (MEPI) and the Nursing Education Partnership Initiative (NEPI) to the African Forum for Research and Education in Health (AFREhealth) - Nelson K. Sewankambo; Peter Donkor (Ubiquity Press, 2018)
The US Government funded Medical Education Partnership Initiative (MEPI) and the Nursing Education Partnership Initiative (NEPI) were large undertakings that introduced major creative changes and innovations in the approach to education of health professions and research in the participating medical and nursing institutions. The African-led MEPI Principal Investigators' (PI) Council which provided strong leadership resolved not to lose momentum but to scale up beyond the MEPI and NEPI institutions and continue with shared learning and the transformative changes that had emerged. The Council started a multi-professional platform which would facilitate and support inter-professional collaboration as the best way forward in the post-MEPI and NEPI period. The African Forum for Research and Education in Africa (AFREhealth) was started and will have to show the value addition it brings and how it will ensure its own sustainability while strengthening South to South partnerships.